USE OF PARTIAL QUALITY FUNCTION DEPLOYMENT TO IDENTIFY PROCESSES REQUIRED FOR ISO 9001 - Cruz-Domínguez, Oscar; Guirette-Barbosa, Omar-Alejandro; Carrera-Escobedo, Jose-Luis; Duran-Muñoz, Hector-Antonio; Guzman-Valdivia, Cesar-Humberto; Ruelas-Santoyo, Edgar-Augusto (The South African Journal of Industrial Engineering, 2021)
This paper proposes an objective way to identify the necessary processes of a quality management system (QMS) to enhance customer satisfaction by meeting customer requirements (CRs). This quality function deployment (QFD)-based method helps to address the implementation of process management, which is a mandatory requirement of modern standards based on QMS, such as ISO 9001 and other international standards. Currently, this identification of processes is made through subjective judgements derived from observation, brainstorming, debates, group projects, and other techniques; but this research presents a standardised way of determining or identifying the processes. The proposed method achieves the identification only of the processes that influence customer satisfaction, consolidating it as a crucial tool in the robust QMS design. The results indicate that the method shown can serve as a platform for subsequent activities, such as process mapping, indicator creation, procedure writing, and other important documents. The purpose of this paper is to show the feasibility of the proposed method, finishing with a summary of the results achieved in a Mexican company’s QMS identification of processes.